A study on mathematics anxiety and its manifestations in vocational high school students - Nur Sahidah; Betty Kusumaningrum; Annis Deshinta Ayuningtyas; Zainnur Wijayanto; Patrick Bergman (Universitas Sarjanawiyata Tamansiswa, 2025)
Mathematics is often perceived as a difficult subject that triggers anxiety, especially among students facing academic pressure. This study aims to analyze and describe the level of mathematics anxiety experienced by final-year vocational high school students. Employing a descriptive qualitative approach, data were collected through a questionnaire distributed to six randomly selected Grade XII students from a vocational school in Gedangsari. The instrument consisted of 23 statements: 6 positive and 17 negative using a Likert scale to assess students’ anxiety. Data analysis followed the Miles & Huberman model, which includes data reduction, display, and verification. The results showed varying levels of mathematics anxiety: 2 students were categorized as having very high anxiety, 3 were in the moderate category, and 1 student experienced very low anxiety. Students with high anxiety reported symptoms such as trembling hands, increased heart rate, mental blocks, and a lack of confidence during mathematics tasks. Meanwhile, students with lower anxiety demonstrated greater emotional control, focus, and proactive engagement in learning activities. The findings indicate that mathematics anxiety can significantly hinder students’ cognitive and emotional capacity to learn effectively. This study contributes to educational psychology by providing insight into how mathematics anxiety manifests among vocational high school students. It highlights the importance of recognizing emotional factors in learning, particularly in high-pressure academic contexts. The results can inform teachers, counselors, and curriculum designers in developing supportive strategies to reduce anxiety and enhance mathematical engagement in vocational education. In conclusion, addressing mathematics anxiety is crucial for fostering a positive and supportive learning environment that empowers students to perform better academically. This research contributes to the understanding of mathematics anxiety in vocational education and emphasizes the need for empathetic, emotion-sensitive teaching approaches that support both cognitive and emotional student development.